2002
DOI: 10.2527/2002.8041105x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of distillers grains from the fermentation of sorghum or corn in diets for finishing beef and lactating dairy cattle

Abstract: Beef finishing and dairy lactation experiments were conducted to evaluate the nutritional value of distillers grains (DG) from sorghum or corn fermentation, in both wet (35.4% DM) and dry (92.2% DM) form (dairy trial only). In the finishing experiment, 60 yearling steers were used in a completely randomized design with three diets that were fed for 127 d: 1) control diet with 86% (DM basis) dry-rolled corn and no DG; 2) 30% of ration DM as wet corn DG in place of dry-rolled corn; and 3) 30% of ration DM as wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
88
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 19 publications
16
88
10
Order By: Relevance
“…According to Al-Suwaiegh et al [25] and Anderson et al [30], the percentage of protein and lactose in milk in cows fed DDGS is similar to those fed WDGS. The growth in milk production and the percentage of casein fraction after the inclusion of DDGS in the feed ration of milking cows in the early stages of lactation have been shown (Figure 3) [20].…”
Section: Frontiers In Bioenergy and Biofuelsmentioning
confidence: 93%
“…According to Al-Suwaiegh et al [25] and Anderson et al [30], the percentage of protein and lactose in milk in cows fed DDGS is similar to those fed WDGS. The growth in milk production and the percentage of casein fraction after the inclusion of DDGS in the feed ration of milking cows in the early stages of lactation have been shown (Figure 3) [20].…”
Section: Frontiers In Bioenergy and Biofuelsmentioning
confidence: 93%
“…Al-Suwaiegh et al (2002) attributed 42% of the overall improvement in NE g content of the diets to the fat content of distillers grains. The authors suggested that the remaining 58% may be attributed to the additions of yeast and yeast byproducts, excess protein used for energy, added moisture, cofactors, differences in the non-fiber carbohydrate fraction, or a reduction in subacute acidosis.…”
Section: Methodsmentioning
confidence: 99%
“…It has not been sufficiently investigated if all kinds of DDGS are equally applicable to RSM, rapeseed expellers or soyabean meal in rations of high-yielding dairy cows, especially when high proportions of DDGS are used. Investigations on the nutrient value of distillers dried grains mainly originate from the USA and therefore are predominately based on maize as the raw material (Palmquist and Conrad, 1982;Van Horn et al, 1985;Powers et al, 1995;Al-Suwaiegh et al, 2002;Anderson et al, 2006;Kleinschmit et al, 2007;Janicek et al, 2008). Only a few studies exist on the equivalent applicability of DDGs from wheat or wheat and barley in dairy cow feeding (Dunkel, 2005;Spiekers et al, 2006;Urdl et al, 2006;Ettle, 2007).…”
Section: Introductionmentioning
confidence: 99%